2021
DOI: 10.1016/j.jhsa.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Ulnar Insertion of the Triangular Fibrocartilage Complex and Related Osseous Landmarks

Abstract: Purpose In triangular fibrocartilage complex (TFCC) injuries, a foveal tear of the radioulnar ligament often requires surgery. Previous studies have suggested that surgeons should attach the TFCC to the center of the fovea. The TFCC and its insertion points are small structures, and few studies have reported details of the foveal insertion. This study aimed to clarify the morphology of the ulnar insertion of the TFCC and related osseous landmarks with 3-dimensional imaging. Methods This study used 26 formalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The concept of foveal repair for Atzei class 2 complete tear or Atzei class 3 proximal tears [ 8 ] explained the inconsistent surgical results after capsular repair for Palmar 1B tear lesions with DRUJ instabilities [ 17 ]. Arthroscopic transosseous suture method was first introduced by Iwasaki in 2009 with single suture strand [ 18 ] and further modified with more comprehensive suture configuration [ 19 ] as recent cadaveric studies demonstrated the three-dimensional morphology of the TFCC foveal insertion [ 20 , 21 ]. Arthroscopic suture anchor repair utilizes one to two non-absorbable sutures to reattach the disrupted TFCC proximal limb to the anchoring fovea insertion site.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of foveal repair for Atzei class 2 complete tear or Atzei class 3 proximal tears [ 8 ] explained the inconsistent surgical results after capsular repair for Palmar 1B tear lesions with DRUJ instabilities [ 17 ]. Arthroscopic transosseous suture method was first introduced by Iwasaki in 2009 with single suture strand [ 18 ] and further modified with more comprehensive suture configuration [ 19 ] as recent cadaveric studies demonstrated the three-dimensional morphology of the TFCC foveal insertion [ 20 , 21 ]. Arthroscopic suture anchor repair utilizes one to two non-absorbable sutures to reattach the disrupted TFCC proximal limb to the anchoring fovea insertion site.…”
Section: Discussionmentioning
confidence: 99%
“…With a small bone tunnel located at the radial border of the fovea, the four sutures pass in different directions to compress the TFCC stump, including both the anterior and dorsal components, to its footprint in a large fan-shaped area, thus obtaining a larger ligament–bone contact surface for healing. The ligament–bone contact surface should cover most of the normal footprint (Figure 6) based on the findings of recent cadaveric studies about the three-dimensional morphology of the TFCC foveal insertion (Okuda et al., 2021; Shin et al., 2017). In addition, the repair tension is shared by the four sutures instead of only the one or two sutures used in other techniques, thus reducing the stress on each suture and theoretically reducing the risk of sutures cutting through the TFCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the technical side, if the repair is eccentric and not at the isometric footprint, or if the repair attaches the TFCC to a wider area than the anatomical footprint, then there would be excessive tension on either the dorsal or volar distal radioulnar ligaments, or both, which would restrict rotational motion. An anatomical study recommends placement of the tunnel at the lowest point of the ulnar fovea, which although is not the centre of the footprint, correlates best with the attachment of the deep component of the TFCC (Okuda et al., 2021). A C-ring targeting drill guide can facilitate accurate placement of bone tunnel.…”
Section: Complications Related To Repair Of An Ulnar-sided Tfcc Tearmentioning
confidence: 99%